Reduced FAF1 Expression and Helicobacter Infection: Correlations with Clinicopathological Features in Gastric Cancer. (11th December 2012) - Liu, Ai-qun; Ge, Lian-ying; Ye, Xin-qing; Luo, Xiao-ling; Luo, Yuan
Abstract : Background. This study aimed to investigate possible associations between FAF1 expression and aspects of gastric cancer, in particular its clinical characteristics and Helicobacter infection. Materials and Methods. RT-PCR and immunohistochemistry were used to analyze expression of FAF1 mRNA and protein in 40 gastric cancer patients. H. pylori infection was detected by three staining protocols. Results. The expression level of FAF1 mRNA was significantly lower in gastric cancer tissue than in normal gastric mucosa from the same patient (P < 0.05 ). FAF1 mRNA expression was significantly lower in stage IV gastric cancer than in stage I+II or IIIA+IIIB (P = 0.004 ) and also significantly lower in gastric cancer with distant metastasis. FAF1 mRNA expression was higher in well-differentiated cancer than in poorly-differentiated cancer (0.39 ± 0.06 versus 0.19 ± 0.06, t = 9 . 966, P < 0 . 01 ). FAF1 protein was detected in 15 of 40 (37.5%) cancerous tissue samples and in 29 of 40 (72.5%) corresponding normal tissue samples (P < 0.01 ). FAF1 mRNA expression was lower in H. pylori -positive cancerous tissue samples than in H. pylori -negative ones (P < 0.05 ). Conclusions. Downregulation of FAF1 expression may be related to the carcinogenesis and progression of gastric cancer, and H. pylori infection during gastric carcinogenesis may downregulate FAF1 expression.